Reduction and prediction of N2O emission from an Anoxic/Oxic wastewater treatment plant upon DO control and model simulation. (November 2017) - Sun, Shichang; Bao, Zhiyuan; Li, Ruoyu; Sun, Dezhi; Geng, Haihong; Huang, Xiaofei; Lin, Junhao; Zhang, Peixin; Ma, Rui; Fang, Lin; Zhang, Xianghua; Zhao, Xuxin
Highlights: The N2 O emission factor of A/O WWTP was 1.60% of N-load. A proper control of DO could remarkably reduce N2 O emission in A/O process. A BP-ANN model simulating N2 O emission from A/O process was established. The two-hidden-layers model could achieve a good prediction of N2 O emission. Abstract: In order to make a better understanding of the characteristics of N2 O emission in A/O wastewater treatment plant, full-scale and pilot-scale experiments were carried out and a back propagation artificial neural network model based on the experimental data was constructed to make a precise prediction of N2 O emission. Results showed that, N2 O flux from different units followed a descending order: aerated grit tank > oxic zone ≫ anoxic zone > final clarifier > primary clarifier, but 99.4% of the total emission of N2 O (1.60% of N-load) was monitored from the oxic zone due to its big surface area. A proper DO control could reduce N2 O emission down to 0.21% of N-load in A/O process, and a two-hidden-layers back propagation model with an optimized structure of 4:3:9:1 could achieve a good simulation of N2 O emission, which provided a new method for the prediction of N2 O emission during wastewater treatment.